Prehospital point of care ultrasound in Helicopter Emergency Medical Services: a 5-year experience study in Belgium - Betz, Romain; Gilbert, Allison; Moens, Didier; Marissiaux, Laurent; Paquay, Meryl; Lopez Iglesias, Raphaëlle; Pirotte, Olivier; Ghuysen, Alexandre; Stipulante, Samuel (Frontiers in Disaster and Emergency Medicine, 2024)
The utilization of Clinical Ultrasound (CUS) in Helicopter Emergency Medical Services (HEMS) has become increasingly prevalent, reflecting its significant role in emergency care.. This descriptive, monocentric study, conducted at the Helicopter Medical Center (CMH) of Bra-sur-Lienne, Belgium, aimed to describe the use of CUS within HEMS and evaluate its potential impact on diagnostic accuracy, therapeutic interventions, and hospital destination decisions. Over a five-year period, from January 2018 to December 2022, our retrospective analysis included 6126 HEMS interventions, with CUS performed in 29.55% of cases. The study demonstrated that CUS led to therapeutic changes in 30.88% of instances and affected the hospital destination in 9% of cases, despite a potential bias towards directing patients to the University Hospital Center of Liège (CHU of Liège) due to operational constraints. The agreement between prehospital CUS findings and hospital imaging was substantial, with an 80.39% concordance rate, underscoring CUS's utility in enhancing prehospital diagnostic accuracy. We found no significant increase in on-scene time due to CUS usage, with most exams completed in less than five minutes.Our findings highlight the interesting role of CUS in HEMS, facilitating more informed and confident medical decision-making in prehospital emergency care. However, variability in CUS application emphasize the need for standardized guidelines to optimize its use. The study's limitations include its retrospective, monocentric design and the focus on on-scene ultrasound evaluations. Future research should aim at a more extensive, prospective analysis to further validate the benefits of CUS in emergency medical services.